(untitled) (International Journal of Engineering and Computer Science, 2019)
By 2019, the management of drilling fluids for high-pressure, high-temperature (HPHT) wells had become a critical focus area for offshore and swamp well operations, particularly in challenging environments such as the Kolocreek and Koroama fields. The extreme conditions of HPHT wells pose significant challenges, including maintaining well stability, ensuring operational safety, and adhering to environmental standards. This study examines these challenges and evaluates the innovative use of specialized mud systems, including reservoir drill-in fluids (RDIF), steel seal pills, and thixsal muds, which were emerging as advanced solutions at the time. Drawing on lessons learned from the design, implementation, and quality control processes of these systems, this research underscores the role of tailored drilling fluid technologies in optimizing cost-effectiveness, enhancing safety, and achieving regulatory compliance. The findings from this study provide a snapshot of the industry’s state in 2019, offering insights into the evolving strategies for managing HPHT wells and setting a foundation for future advancements in drilling fluid technologies.